The Effect of Balance Exercises and Mozart Music Therapy on Elderly Anxiety and Balance - Mubayinul Khoeroh (GLOBAL HEALTH SCIENCE GROUP, 2026)
Many elderly individuals deal with anxiety about their declining bodies and fears of social isolation. Such changes can contribute to a decline in the quality of life in multiple dimensions. The study incorporated 12 balance exercises to enhance one’s balance and decrease the risk of falls. To address anxiety, the research utilized Mozart’s classical music therapy. Music has the ability to heal and restore the body, mentally and physically, and stimulate the production of calming endorphins. The study’s aim was to evaluate the effect of 12 balance exercises and Mozart classical music therapy to elders in determining the risk of falling and the level of anxiety. Quasi-experimental 2 groups, control and treatment. The sample was 28 elders. The control group, consisting of 14 people, only received the music therapy, while the treatment group of 14 people received 12 balance exercises along with Mozart music therapy. The intervention was carried out 2 sessions/week for 4 weeks. Data were collected using valid and reliable instruments; the Berg Balance Scale (BBS: r = 0.98; α = 0.97) was used to measure the risk of falling and the Hamilton Anxiety Rating Scale (HARS: r = 0.81; α = 0.92) was used to measure anxiety. Paired t-tests and independent t-tests were used to analyze data and assess pre–post changes and differences within and between groups. The treatment group showed significant improvements in BBS score (p < 0.001) and a significant reduction in HARS scores (p < 0.001) in contrast to the control group. In conclusion, 12 Balance Exercises and Mozart music therapy improved balance and reduced anxiety in elderly people.